The fearless organization eaudiobook Creating psychological safety in the workplace for learning, innovation, and growth. - Edmondson, Amy C. (Ascent Audio, 2019)
The Fearless Organization offers practical guidance for teams and organizations who are serious about success in the modern economy. With so much riding on innovation, creativity, and spark, it is essential to attract and retain quality talent—but what good does this talent do if no one is able to speak their mind? The traditional culture of "fitting in" and "going along" spells doom in the knowledge economy. Success requires a continuous influx of new ideas, new challenges, and critical thought, and the interpersonal climate must not suppress, silence, ridicule or intimidate. Not every idea is good, and yes there are stupid questions, and yes dissent can slow things down, but talking through these things is an essential part of the creative process. People must be allowed to voice half-finished thoughts, ask questions from left field, and brainstorm out loud; it creates a culture in which a minor flub or momentary lapse is no big deal, and where actual mistakes are owned and corrected, and where the next left-field idea could be the next big thing. This book explores this culture of psychological safety, and provides a blueprint for bringing it to life. The road is sometimes bumpy, but succinct and informative scenario-based explanations provide a clear path forward to constant learning and healthy innovation.